Mathematical communication ability of 7th grade students viewed from indonesian language ability in experiential learning model - Sari, Intan; Suyitno, Hardi (Department of Mathematics, Universitas Negeri Semarang, 2019)
Communication ability need to be improved so that students can solve math problems well. This study aims to determine 1) the completeness of learning mathematics communication 7th grade students with experiential learning models; 2) the influence of Indonesian language ability on mathematical communication ability; 3) mathematical communication ability of students who have very high Indonesian language ability; 4) mathematical communication ability of students who have high Indonesian language ability; 5) mathematical communication ability of students who have medium Indonesian language ability. This study uses a combination method. The population in this study is 7th grade students in one of the junior high schools in the city of Semarang year 2018/2019. Sampling by random sampling technique and subject selection with purposive sampling technique. The results show that (1) mathematical communication ability of 7th grade students with experiential learning models can achieve learning completeness; (2) there is an influence of Indonesian language ability on students' mathematical communication ability in the experiential learning model; (3) students with very high Indonesian language ability have been able to reach all indicators of written communication ability; (4) students with high Indonesian language ability have been able to reach all indicators of written mathematical communication ability even though there are still errors in making conclusions; (5) students with medium Indonesian language ability are only able to master two indicator of written mathematical communication ability.